The Utility of Independent Component Analysis and Machine Learning in the Identification of the Amyotrophic Lateral Sclerosis Diseased Brain - Welsh, Robert C.; Jelsone-Swain, Laura M.; Foerster, Bradley R. (Frontiers in Human Neuroscience, 2013)
Amyotrophic lateral sclerosis (ALS) is a devastating disease with a lifetime risk of approximately 1 in 2000. Presently diagnosis of ALS relies on clinical assessments for upper motor neuron and lower motor neuron deficits in multiple body segments together with a history of progression of symptoms. In addition, is it common to evaluate lower motor neuron pathology in ALS by electromyography. However, upper motor neuron pathology is solely assessed on clinical grounds hindering diagnosis. In the past decade magnetic resonance methods have been shown to be sensitive to the ALS disease process, namely: resting state connectivity measured with functional MRI, cortical thickness measured by high resolution imaging, diffusion tensor imaging (DTI) metrics such as fractional anisotropy (FA) and radial diffusivity (RD), and more recently magnet resonance spectroscopy measures of gamma-aminobutyric acid (GABA) concentration. In this present work we utilize independent component analysis (ICA) to derive brain networks based on resting state functional magnetic resonance imaging and use those derived networks to build a disease state classify using machine learning (support-vector machine). We show that it is possible to achieve over 71% accuracy for disease state classification. These results are promising for the development of a clinically relevant disease state classifier. Future inclusion of other MR modalities such as high resolution derived cortical thickness, DTI metric and MRS should improve this overall accuracy.